Genetic Characterization of Protein C Deficiency in Japanese Subjects Using a Rapid and Nonradioactive Method for Single-Strand Conformational Polymorphism Analysis and a Model Building - Miyata, Toshiyuki; Sakata, Toshiyuki; Zheng, Yan-Zhen; Tsukamoto, Hiroaki; Umeyama, Hideaki; Uchiyama, Shinichiro; Ikusaka, Masaomi; Yoshioka, Akira; Imanaka, Yasufumi; Fujimura, Hironobu; Kambayashi, Jun-ichi; Kato, Hisao (Thrombosis and Haemostasis, 1996)
We studied the molecular basis of protein C deficiency in 28 Japanese families including 4 asymptomatic families. Two showed a decreased level of function with a normal antigen concentration consistent with type II protein C deficiency and the remaining 26 showed type I deficiency with decreases in both function and antigen level. All the exons and intron/exon junctions of the protein C gene were studied using a strategy combining polymerase chain reaction (PCR) amplification and rapid nonradioactive single-strand conformational polymorphism (SSCP) analysis. The PCR-amplified fragments with aberrant migration on SSCP analysis were sequenced. We identified 11 missense mutations, 1 nonsense mutation, 2 neutral polymorphisms, 1 frameshift deletion, 1 inframe deletion, and 1 splice site mutation. We also identified two different rare mutations in the 5-untranslated region in the protein C gene that may be responsible for the phenotype. Of these molecular defects, ten were novel. From the results of genetic analysis of 47 Japanese families with protein C deficiency reported in this and previous studies, Phel39Val and Met364Ile substitutions and a G8857 deletion were only found in Japanese subjects and seem to be a founder effect. In contrast, Argl69Trp and Val297Met substitutions, both occurring at CG dinucleotides, were commonly observed in not only Japanese but also Western populations, indicating that these are hot spots for mutation in the protein C gene. These molecular defects were found in 22 families in total, accounting for 47% of Japanese families with protein C deficiency. The structural models of the second EGF and protease domains of activated wild-type and mutant human protein C suggest a possible substrate binding exosite on two loops; one from amino acid position 349 to 357 and the other from position 385 to 388, both of which are close to each other in the three-dimensional model.